Effects of ex vivo blood anticoagulation and preanalytical processing time on the proteome content of platelets. (17th March 2022) - Tassi Yunga, Samuel; Gower, Austin J.; Melrose, Alexander R.; Fitzgerald, Meghan K.; Rajendran, Ashmitha; Lusardi, Theresa A.; Armstrong, Randall J.; Minnier, Jessica; Jordan, Kelley R.; McCarty, Owen J. T.; David, Larry L.; Wilmarth, Phillip A.; et al.
Abstract: Background: Ex vivo assays of platelet function critically inform mechanistic and clinical hematology studies, where effects of divergent blood processing methods on platelet composition are apparent, but unspecified. Objective: Here, we evaluate how different blood anticoagulation options and processing times affect platelet function and protein content ex vivo . Methods: Parallel blood samples were collected from healthy human donors into sodium citrate, acid citrate dextrose, EDTA or heparin, and processed over an extended time course for functional and biochemical experiments, including platelet proteome quantification with multiplexed tandem mass tag (TMT) labeling and triple quadrupole mass spectrometry (MS). Results: Each anticoagulant had time‐dependent effects on platelet function in whole blood. For instance, heparin enhanced platelet agonist reactivity, platelet‐monocyte aggregate formation and platelet extracellular vesicle release, while EDTA increased platelet α‐granule secretion. Following platelet isolation, TMT‐MS quantified 3357 proteins amongst all prepared platelet samples. Altogether, >400 proteins were differentially abundant in platelets isolated from blood processed at 24 h versus 1 h post‐phlebotomy, including proteins pertinent to membrane trafficking and exocytosis. Anticoagulant‐specific effects on platelet proteomes included increased complement system and decreased α‐granule proteins in platelets from EDTA‐anticoagulated blood. Platelets prepared from heparinized blood had higher levels of histone and neutrophil‐associated proteins in a manner related to neutrophil extracellular trap (NET) formation and platelet:NET interactions in whole blood ex vivo . Conclusion: Our results demonstrate that different anticoagulants routinely used for blood collection have varying effects on platelets ex vivo, where methodology‐associated alterations in platelet proteome may influence mechanistic, translational and biomarker studies.